Bringing regional politics to the study of security sector reform: Army reform in Sierra Leone and Iraq - Selman Almohad (German Institute of Global and Area Studies (GIGA), 2019)
This paper argues that the scholarship on security sector reform (SSR) tends to neglect regional politics in the formulation of its concepts and policies, and that this neglect deprives the study of SSR of a valuable analytical level. It therefore uses comparative historical analysis and the model of regional conflict formations (RCFs) to examine army reforms in Sierra Leone and Iraq from a regional angle, thereby illustrating the explanatory potential that regional politics could bring to the study of SSR and its implementation. The paper also distinguishes between convergent and divergent regional formations, whereby the relationship between SSR outcomes and regional politics is conceived of as constitutive, entangled, and holistic.
Keywords: 300; security sector reform (SSR); statebuilding; regional politics; army reform; Iraq; Sierra Leone; comparative historical analysis